The Antibiotic Resistance-Related Indicators In Campylobacter Species Isolated From Water And Retail Fresh Milk Samples In Southern Iraq - Huda Jihad G (Academia One, 2025)
Campylobacter species are prominent bacteria associated with human gastrointestinal diseases and are primarily present in the faeces of domestic animals, sewage discharge and agricultural runoff. These viruses have been linked to disease outbreaks resulting from the intake of contaminated water and milk in many regions of the world. However, there is a lack of detailed reports on this issue in the Misan Governorate. Therefore, this study assessed the prevalence, pathogenicity and antibiotic resistance markers of Campylobacter species isolated from water and milk samples. A combined total of 70 raw milk samples and 57 water samples were gathered. These samples were subjected to enrichment in Bolton broth and then incubated for 48 h at 42 °C in a 10% CO2 environment with limited oxygen. Subsequently, the cultures that had been enriched were subjected to additional processing and purification. Campylobacter colonies that were likely to be present were separated and verified by PCR using specialised primers designed to identify the Campylobacter genus, specific species and genes linked with virulence. The antimicrobial resistance profiles of the isolates were examined using the disc diffusion method against a panel of 12 antibiotics. The presence of important genotypic resistance genes was assessed by PCR. A total of 309 presumptive Campylobacter isolates were collected, of which 180 were confirmed to be from the Campylobacter genus
Keywords: Resistance-Related; Campylobacter; Water; Fresh Milk